Speed Adjustment on Variable Frequency Induction Motor Using PLC for Automatic Polishing Machine - Agung Prasetyo Utomo; Anggara Trisna Nugraha (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2021)
PT. ROFENTI KARSA TAMA is a ceramic industry that produces products in the form of ceramics from natural stone which are addressed in Winong GEMPOL Village - MALANG. To produce a perfect ceramic process requires absolutely reliable electrical and mechanical equipment. In an automatic system a frequency converter is used as a speed regulator, because in a manual system using a grinder, the capacity is only 0.57Kw (kilowatts), and the production effect is not good. Therefore, the purpose of this study is to design an automatic polishing machine using a PLC-based converter. Based on the PLC, the capacity is 5 or 5 Kw (kilowatts). This system can increase ceramic output and improve quality. In this case, assuming that the operator usually uses an automatic system to complete the work of the three operators, the polishing machine production costs can be reduced. Through system improvement, production quality can be improved, manual polishing operators can only produce 480 pieces per day, while the automatic system can produce 1,536 pieces. One day, the polishing operator will save production costs of Rp 2.7 million per month.